Acorn: Developing full-chain industrial carbon capture and storage in a resource- and infrastructure-rich hydrocarbon province. (1st October 2019) - Alcalde, Juan; Heinemann, Niklas; Mabon, Leslie; Worden, Richard H.; de Coninck, Heleen; Robertson, Hazel; Maver, Marko; Ghanbari, Saeed; Swennenhuis, Floris; Mann, Indira; Walker, Tiana; Gomersal, Sam; et al.
Abstract: Research to date has identified cost and lack of support from stakeholders as two key barriers to the development of a carbon dioxide capture and storage (CCS) industry that is capable of effectively mitigating climate change. This paper responds to these challenges through systematic evaluation of the research and development process for the Acorn CCS project, a project designed to develop a scalable, full-chain CCS project on the north-east coast of the UK. Through assessment of Acorn's publicly-available outputs, we identify strategies which may help to enhance the viability of early-stage CCS projects. Initial capital costs can be minimised by infrastructure re-use, particularly pipelines, and by re-use of data describing the subsurface acquired during oil and gas exploration activity. Also, development of the project in separate stages of activity (e.g. different phases of infrastructure re-use and investment into new infrastructure) enables cost reduction for future build-out phases. Additionally, engagement of regional-level policy makers may help to build stakeholder support by situating CCS within regional decarbonisation narratives. We argue that these insights may be translated to general objectives for any CCS project sharing similar characteristics such as legacy infrastructure, industrial clusters and an involved stakeholder-base that is engaged with the fossil fuel industry. Highlights: Cost reduction and stakeholder support are essential for CCS industry development. Acorn is aimed to develop a full-chain CCS system at minimum cost by the 2020s. Infrastructure re-use and staged investment and development enable cost reduction. Stakeholder and local community engagement is key to promote a just transition. The Acorn experience can be implemented in regions with similar CCS needs.